Importance of corporate governance in state-owned television corporations: the case of RTVE - Ojer, Teresa (Anàlisi, 2011)
The corporate governance of a company is a key factor in the performance of its activities. Despite its importance, however, corporate governance surprisingly remains one of the least studied aspects in the literature on media economics and management, more so taking into account that the decisions adopted by company executives may affect the content of the media and its ability to fulfil its social responsibility. Accordingly, this article seeks to highlight the importance of corporate governance in state-owned television stations, and in particular, to study the implications that the selection and composition of the governing body of Spanish Public Television (RTVE) has had for the broadcaster’s operation, independence and management over the last thirty years.